2020
DOI: 10.1002/lsm.23225
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Response to Photobiomodulation—Why Some Respond and Others Do Not: A Randomized Controlled Study

Abstract: Conclusions: We demonstrated that PBM induces arteriolar vasodilatation that results in both immediate and long-lasting increased capillary flow and tissue perfusion in healthy individuals. This response was wavelengthdependent and modified by skin temperature. These findings regarding physiological parameters associated with sensitivity or resistance to PBM provide information of direct relevance for patient-specific therapy. Lasers Surg. Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 51 publications
3
25
0
1
Order By: Relevance
“…Previous studies have shown that PBM induces vasodilatation in healthy volunteers [51] and treated patients [52]. In the current study, Ang-II-induced SMC contraction was terminated by PBM and was prevented by preincubation with estrogen.…”
Section: Smc Contraction and Mitochondrial Dispersionsupporting
confidence: 57%
“…Previous studies have shown that PBM induces vasodilatation in healthy volunteers [51] and treated patients [52]. In the current study, Ang-II-induced SMC contraction was terminated by PBM and was prevented by preincubation with estrogen.…”
Section: Smc Contraction and Mitochondrial Dispersionsupporting
confidence: 57%
“…For clinical details, see Table 1 Table 1 patient exposure to the hospital environment in light of coronavirus disease (COVID- 19) or other potential infection in immunocompromised cancer patients. PBM was shown to be beneficial for acceleration of healing of both acute and chronic wounds [5] based on its ability to enhance the microcirculatory flow [23] and to stimulate the mitochondria energetic state even in stressed conditions [24,25]. Particularly, the PBM protocol (and the same device) used in this study was previously reported to accelerate healing of diabetic foot ulcers [15,16] and to prevent post-laminectomy scar formation when used as a preventive measure [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a prospective, randomized, and controlled clinical trial [34] evaluated 20 healthy young participants, non-smokers, for a time of 5 min. They investigated the effects of irradiation in the wrist region, including the ulnar and radial arteries, of a cluster composed of red LEDs (wavelength in 633 nm, power density of 70 mW/cm 2 and delivered energy density of 21 J/cm 2 ) or infrared (wavelength of 830 nm, power density of 55 mW/cm 2 and delivered energy density of 16.5 J/cm 2 ).…”
Section: Hemodynamics Effectsmentioning
confidence: 99%